Evolution and the origin of life - Lazarus, Tom; Road, Mike; CRM Productions (Del Mar, Calif. : CRM/McGraw-Hill Films, 1972)
Uses cinemicroscopy, time-lapse photography, special effects, animation, macro-photography, documentary and nature footage to survey the history of the earth from its beginning. Topics represented includes DNA, bacteria photosynthesis, flagellates, sexual reproduction, multicellular colonies and etc.
APD 01719
Copy available in DVD format
Keywords: Life -- Origin; Evolution